L’apologetica in "Epilogo" di Hans Urs von Balthasar - Villagrasa LC, Jesús (Alpha Omega, 2011)
After establishing von Balthasar’s place in twentieth-century fundamental theology, the article presents the general outlines of his wor and, therefore, to some degree, his apologetics. This is done by explaining some structural features of three brief works: Razing the Bastions: On the Church in this Age (1952) which constitutes the pars destruens and clears the basis on which to build; Love Alone is Credible (1965) which represents the pars construens and was written when some volumes of Gloria had already been published; and finally, Epilogue (1987) which provides the final justification for the edifice. The article con-cludes with a presentation of the “insufficient but necessary” apologetics from the first part of the Epilogue.